Identification of information resource structure problems in the information searching process - Kostenko, V. V.; Kostenko, D. Ye.; Zamotaiev, Ye. D.; Shyrochenko, V. O. (Systems and Technologies, 2019)
There are investigated important problems of the information search process. Long-term accumulation of information has its negative sides. The main problem is the glut of so-called “digital noise”. “Digital noise” is information which doesn’t assist the user in information searching process. “Digital noise” makes it difficult to find the right answer. At the same time there is another prob-lem – the number of materials that are freely available is constantly growing, doubling on average once every 2 years. Sometimes – more often. In this growth there are hidden one of the main problems. Finding the right information often turns into a difficult problem that takes time and effort. There are shown the main differences between the search (as an automatical procedure) and the necessary information allocation. Identified some questions which appropriate to analyze when solving a search problem or highlighting the necessary information (site content, data storage and processing methods, site values for information support of the relevant type of activity). The main idea of this article is in optimize the fil-tering and retrieving information process for users. It is necessary to hide from the user information which doesn’t solve his problems. There are create a test-software module which solve some problems described in this article. Revealed the main points of implementation the selection mechanism of the necessary information. The idea is in allocate absolutely or most useful answers. It wouldn’t be necessary to re-read or scroll through the whole discussion board to find out what is the ultimate correct answer or the right decision. Recommendations and suggestions are given to solve the problem of finding the necessary information for the user among a large amount of “information noise”. It is necessary to create the more specialized and thematic resources with high-quality content. Using this portals, the information searching will be faster and better. It’s necessary to develop comparison services. If it pos-sible, there are necessary to use geolocation services and base searching process on user’s location. It is necessary to emphasize the quality of information and di-vide it according to the tasks.